ISLAM NORMATIF : EPISTIMOLOGI BAYANI DALAM STUDI ISLAM - Izzatun Naimah (Al Jabiri: Jurnal Ilmiah Studi Islam, 2022)
In studying science, we cannot be separated from what is called the source of knowledge in this case, namely the Al-Quran and Hadith. These two sources are the most important human foundation in the policies that will be taken. Because the two sources of this book, namely the Al-Quran and Hadith, are the two most important sources of law that are used as the basis for the theory of Muslims in making decisions. We cannot take decisions without a clear basis unless he is a Prophet. In this article I will discuss how important the bayani approach is in practice in making decisions for legal steps to be taken. Bayani epistemology is an approach that emphasizes the texts or texts of the Qur'an as a guide. In Islamic normative studies, the bayani approach becomes a very important legal guideline in accordance with its usefulness as a source of law and legal basis